Negative Poisson's ratio in rippled graphene. Issue 12 (10th March 2017) - Qin, Huasong; Sun, Yu; Liu, Jefferson Zhe; Li, Mengjie; Liu, Yilun
Abstract : We performed molecular dynamics simulations to investigate the Poisson's ratio of rippled graphene sheets generated by topological defects. Abstract : In this work, we perform molecular dynamics (MD) simulations to study the effect of rippling on the Poisson's ratio of graphene. Due to the atomic scale thickness of graphene, out-of-plane ripples are generated in free standing graphene with topological defects ( e.g. heptagons and pentagons) to release the in-plane deformation energy. Through MD simulations, we have found that the Poisson's ratio of rippled graphene decreases upon increasing its aspect ratio η (amplitude over wavelength). For the rippled graphene sheet η = 0.188, a negative Poisson's ratio of −0.38 is observed for a tensile strain up to 8%, while the Poisson's ratio for η = 0.066 is almost zero. During uniaxial tension, the ripples gradually become flat, thus the Poisson's ratio of rippled graphene is determined by the competing factors of the intrinsic positive Poisson's ratio of graphene and the negative Poisson's ratio due to the de-wrinkling effect. Besides, the rippled graphene exhibits excellent fracture strength and toughness. With the combination of its auxetic and excellent mechanical properties, rippled graphene may possess potential for application in nano-devices and nanomaterials.